The Relationship Between Online Game Addiction and Aggressive Behavior - Widya Khairunnisa; Triyono; Mori Dianto (Journal of Practice Learning and Educational Development, 2026)
This study was motivated by the rampant online game addiction in SMP Negeri 3 Lubuk Sikaping, where some students showed aggressive behaviour such as saying harsh words when disturbed by playing and hitting friends when losing the game. The purpose of this study is to describe: (1) the level of online game addiction, (2) the level of aggressive behaviour, and (3) the relationship between online game addiction and aggressive behaviour. The study used a quantitative approach with a correlational type. The population was 90 students, with a sample of 60 people selected through purposive sampling technique. The instrument was a questionnaire, and the data was analysed using percentage and correlation tests. The results showed that online game addiction and aggressive behaviour were in the very high category, and there was a fairly strong relationship between the two. These findings emphasise the need for learner awareness, parental supervision, and the active role of counselling teachers in developing appropriate service programmes. Online games are fun, but their effects should be watched out for.